Practice of the city magistrates in Belgrade regarding domestic violence - Anđelković Marija (Temida)
In this paper author analyzes all cases of the city magistrates in Belgrade in 2002 which went into effect. The goal of this analysis is to determine how many cases are related to domestic violence and to define sentencing policy applied in these cases. In this analysis author pointed out problems and needs which exist in the work of the city magistrates. Also, some suggestions and recommendations for overcoming these problems are underlined.